Corelaţia acţiunii civile cu accesul la justiţie [Articol] - Dodica, Ina (CEP USM, 2013)
Access to justice is a core fundamental right and a central concept in the broader field of justice. However, it is a right that faces a number of challenges throughout the national legislation. These challenges appear as impediments of legal, organizational or functional matter.
Keywords: dreptul la apărare